3D printing of liquid metal EGaIn through laser induced forward transfer: A proof-of-concept study. (April 2021) - Vallabh, Chaitanya Krishna Prasad; Xiong, Yubo; Zhao, Xiayun
Abstract: In this work, we introduce Laser Induced Forward Transfer (LIFT) of Liquid Metal (LM) alloys, specifically Eutectic Gallium-Indium (EGaIn). LIFT for LM provides a fairly simple manufacturing method with better control and modularity for patterning LMs compared to existing methods such as imprinting, and extrusion. LIFT is a direct-write printing method which is used for a wide range of applications, such as, laser printing of electronic materials, biomolecules, and cells. Our preliminary results demonstrate great potential of LIFT process for LM deposition and patterning, and can help achieve finer and scalable features with high throughput.